DINAMIKA KELOMPOK WANITA TANI (KWT) REREONGAN DESA CIBURUY KECAMATAN PADALARANG KABUPATEN BANDUNG BARAT - Modjo, Andhika Rangga Kusuma; Setiawan, Iwan (Universitas Galuh, 2023)
Women Farmers Group (KWT) Rereongan (KWT-R) is included in the best KWT in Indonesia. However, in its development, KWT Rereongan faced various problems that disturbed its dynamics. This study aims to analyze group dynamics and social problems in KWT Rereongan. The research was designed qualitatively with a case study approach. Data collection techniques were carried out by carrying out observations and in-depth interviews with three active KWT Rereongan management informants. Data were analyzed by descriptive qualitative. The results of the study show that the dynamics of the KWT Rereongan are in the pre-dynamic category. There are three out of nine elements of group dynamics that are not fulfilled such as group coaching and maintenance, group pressure, and group cohesiveness. This was caused by the existence of conflict among group members caused by bad prejudice and different views on KWT Rereongan funding.